INTRODUKSI TEKNOLOGI PENGOLAHAN TERUNG MENJADI MANISAN DAN DODOL SEBAGAI USAHA SKALA RUMAH TANGGA BAGI KELOMPOK IBU RUMAH TANGGA DI DESA TANJUNG SETEKO KECAMATAN INDRALAYA UTARA OGAN ILIR - Henny Malini (Jurnal Pengabdian Sriwijaya, 2013)
Introduction processing technology eggplant into candy and lunkhead as household scale for the housewife inÂ  Tanjung Seteko village indralaya sub distric Ogan Ilir Regency . This activities aim to 1 ) increase the value added through processing eggplant into candy and lunkhead as an alternative household enterprises that can contribute to the household income . 2 ) increasing the participation of women in the household in order to contribute to the economic needs of the household.Â  in the Tanjung Seteko village many farmers who grow vegetables , one of the main types of vegetables is the most widely planted eggplant , but farmers only sold in fresh form so the price is cheap because there is no added value of these vegetables , such as eggplant cheap market prices , housewives are able to open opportunities is to cultivate a candied and lunkhead. The addition of this knowledge is very useful , it can also be a solution to increase the family income . With this knowledge in addition to make candied eggplant and eggplant lunkhead , mothers can also creation of own flavor and color of the candy and the purple eggplant lunkhead